Body Shaming dalam Al-Qur’an Perspektif Tafsir Maqasidi - Muhammad Mundzir; Arin Maulida Aulana; Nunik Alviatul Arizki (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
Covid-19, Emotional Mental Conditions, Quarantine, Memorizing the Qur'an. This research derives from academic problems such as. Firstly, body shaming is an actual phenomenon, and it is widely discussed. Secondly, the phenomenon of body shaming has occurred in the past until now, but it has different terms these days. Thirdly, the interpretations related to the verse on the term body shaming have not touched the maqasidi aspect and only discussed the prohibition. In this study, the author uses a type of library research and a descriptive method with the Tafsir Maqasidi approach. This approach serves to explore the interpretation of the verse along with the analysis. Maqasidi and its contextualization in the present. This study produced several findings, such as the value of benefit including the value of humanity (speaking human words), the value of justice (every disgraceful behavior will have consequences), and the value of moderation: (saying with respect for the feelings of others). The Maqasidi aspects contained in the prohibition of body shaming are in the form of hifz al-nafs, hifz al-din, and hifz al-‘aql.